MINERALS AND HEAVY METALS CONTENTS OF GLYCYRRHIZA GLABRA L. AND ANDROGRAPHIS PANICULATA (BURM. F.) FROM MEERUT, INDIA - SAMPAT GHOSH,; MANU SINGH, (International Journal of Pharma and Bio Sciences, 2015)
The present study was carried out to estimate the level of nutritionally beneficial minerals viz. calcium (Ca), sodium (Na), potassium (K), Magnesium (Mg), iron (Fe), zinc (Zn), copper (Cu) as well as four potential toxic heavy metals namely nickel (Ni), arsenic (As), lead (Pb) and cadmium (Cd) in root of Glycyrrhiza glabra L. (Fabaceae) and stem of Andrographis paniculata (Burm. f.) Nees. (Acanthaceae). The air dried powdered materials of the useful plant parts were subjected to wet digestion and were analyzed by using atomic absorption spectrophotometer and flame photometer. The result reveals that both the plants may be used as a good source of minerals and very particularly for iron. It also shows that the levels of four toxic metals in both the medicinal plants were below the permissible limit set by world health organization (WHO).